2015
DOI: 10.5603/fhc.a2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

Application of FISH method for preimplantation genetic diagnostics of reciprocal and Robertsonian translocations

Abstract: Introduction. Carriers of reciprocal (RCP) and Robertsonian (RT) translocations are known to be at risk for reproductive difficulties. Preimplantation genetic diagnosis (PGD) is one of the options these carriers have to try to fulfill their desire to have a child. The FISH technique is one of the best method to detect RCPs, and, together with the Next Generation Sequencing, to diagnose RTs. The aim of the present study was to assess the usefulness of the FISH method for rapid diagnosis of translocations in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Five hundred and forty-eight embryos were biopsied and 101 euploid embryos were found, yielding a euploidy rate of 19.4%. A study carried out by our group examined nine patients with translocations identified with CGH-array and/or NGS tests and found fertilization and euploidy rates of 84% and 38%, respectively, similarly to Liss et al . (2015) .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Five hundred and forty-eight embryos were biopsied and 101 euploid embryos were found, yielding a euploidy rate of 19.4%. A study carried out by our group examined nine patients with translocations identified with CGH-array and/or NGS tests and found fertilization and euploidy rates of 84% and 38%, respectively, similarly to Liss et al . (2015) .…”
Section: Discussionsupporting
confidence: 70%
“… Liss et al . (2015) studied 42 couples with reciprocal translocation and 35 with Robertsonian translocation through the FISH technique.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, carriers can avoid physical and psychological trauma due to recurrent miscarriage or termination of the affected pregnancy upon selective transfer of normal or balanced diploid embryos. Several methods have been applied to PGT-SR, including fluorescence in situ hybridization (FISH) [ 10 , 11 ], single-nucleotide polymorphism (SNP) arrays [ 12 , 13 ], array comparative genomic hybridization (aCGH) [ 8 , 14 ], and next-generation sequencing (NGS) [ 15 17 ]. The initial FISH method is limited to the detection of several specific chromosomes, and the results are sometimes uncertain due to ambiguous optical signals of the fluorescent probes and complex sample preparation procedures [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both male and female carriers of balanced translocations typically do not exhibit any adverse phenotypic effect themselves, but more than 60% of their gametes are predicted to be unbalanced, leading to abnormal embryos. These individuals are therefore at risk for infertility, repeated implantation failures, pregnancy loss, and birth defects [1][2][3][4]. Indeed, while balanced translocations are found in only 0.2% of the neonatal population, the incidence is higher among infertile couples (0.6%) and in women with recurrent miscarriages (9.2%).…”
Section: Introductionmentioning
confidence: 99%